Relationship Between Some Parameters of the Membrane-Redox Potentials Three-State Line System with the Human Constitutional Types of Traditional Medicine (Central Asian Journal of Medical Sciences, 2015)
Objectives: According to Tibetan-Mongolian traditional medicine theory, humans are classified into three main individuals based on the Rlung, Mkhris or Badgan symbolic code (SC). Our objective was to research the relationship between some parameters of membrane-redox potentials three-state line system in relation to the human constitutions of traditional medicine. Methods: The quantities ratio for the SC of Rlung, Mkhris, and Badgan was determined by the Doc-Am-I program. We determined the lipid profile, erythrocyte membrane resistance capacity and body mass index. Results: It was shown that the concentration of serum lipids, body mass index and membrane resistance capacity of individuals of the Badgan SC group was increased with statistical significance in comparison to the other two groups. Our study revealed that people of Rlung SC group were characterized by the highest concentration of malondialdehyde and the lowest rate of membrane resistance capacity compared to people of the other two SC groups. Conclusion: Our study defined the relevance of the membrane redox potentials three-state line system in connection to the human constitutional types such as the abstractly coded classifications of Rlung, Mkhris, and Badgan of traditional medicine.